Overcoming evil genocide, violent conflict, and terrorism - Staub, Ervin (New York ; Oxford : Oxford University Press, 2011)
'Overcoming Evil' describes the origins or influences leading to genocide, violent conflict and terrorism. It identifies principles and practices of prevention, and of reconciliation between groups after violence, or before violence thereby to prevent violence.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Conflict management; Genocide; Violence; Aggressiveness; Social groups